Environmental Wind Engineering and Design of Wind Energy Structures - Baniotopoulos, Charalambos C.; Borri, Claudio; Stathopoulos, Theodore (CISM Courses and Lectures, 2011)
The book presents a state-of-the-art in environmental aerodynamics and the structural design of wind energy support structures, particularly from a modern computational perspective. Examples include real-life applications dealing with pollutant dispersion in the building environment, pedestrian-level winds, comfort levels, relevant legislation and remedial measures. Design methodologies for wind energy structures include reliability assessment and code frameworks.